High-dosage anhydrite-based self-leveling material

Through the preparation and chemical excitation technology of high-addition anhydrous anhydrate combined with other components, the problems of small amount of anhydrous ahydrate and slow hydration rate are solved, and the improvement of material performance and optimization of construction performance are achieved.

CN119797879AInactive Publication Date: 2025-04-11CHANGZHOU ARCHITECTUAL RES INST GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510022287.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anhydrite self-leveling mortar has problems such as small amount of dosage, low utilization rate, slow hydration rate, long settling time and unstable material properties, resulting in poor construction properties and limited application.

Method used

High-dose anhydrous anhydrite is used as the main raw material, combined with 42.5 gray cement, fast hard cement, salt composite exciter, sand, water reducing agent, latex powder, water retention thickener, defoaming agent and other ingredients, and self-leveling dry powder material is prepared by uniform stirring and chemical excitation, and water is added to form agitated.

Benefits of technology

It improves the utilization rate and performance stability of anhydrite, shortens the settling time, enhances the mechanical strength and water resistance of the material, and improves the construction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231730490000021
    Figure BDA0005231730490000021
  • Figure BDA0005231730490000051
    Figure BDA0005231730490000051
  • Figure BDA0005231730490000061
    Figure BDA0005231730490000061
Patent Text Reader

Abstract

The invention belongs to the technical field of building decoration materials, provides a dry powder material which is specially used for ground leveling, is also applied to various base layers such as indoor ground, cement base surfaces and gypsum boards, provides a uniform and smooth surface for the ground and enhances the load bearing and pressure resistance of the ground, and particularly relates to a high-dosage anhydrite-based self-leveling material. The water-retaining mortar is prepared from the following raw materials in parts by mass: 80 parts of II type anhydrous anhydrite, 12 to 16 parts of 42.5 ash cement, 4 to 8 parts of rapid hardening cement, 2.7 to 3.7 parts of salt composite exciting agent, 10 to 16 parts of sand, 0.3 to 0.4 part of water reducing agent, 0 to 1 part of redispersible latex powder, 0.03 to 0.1 part of water-retaining thickening agent and 0.08 to 0.12 part of defoaming agent. According to the invention, the activity of the anhydrite is excited by the sulfate composite activator and the cement alkaline activator, the setting time is shortened, the crystal morphology of a hydration product is changed, and the hydration rate of the anhydrite is improved by doping the salt composite activator, so that the CaSO4. 2H2O crystal content in a hardened body is greatly increased, and the strength of the hardened body is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building decoration materials, in particular to a high-dosage anhydrous hard gypsum-based self-leveling material. Background Art

[0002] Natural anhydrite is mainly formed in inland seas and salt lakes in nature. It is a product of chemical sedimentation. It occasionally appears in hydrothermal and contact metasomatic deposits and volcanic lava holes, often coexisting with gypsum and rock salt. my country has abundant reserves of anhydrite, which has the advantages of simple processing technology, resource saving, utilization of waste residues, and environmental protection.

[0003] Gypsum self-leveling is a dry mortar specially used for ground leveling, which is prepared and evenly mixed in the factory with gypsum materials, special aggregates and a variety of building chemical additives.

[0004] According to the different types of gypsum, the cementing materials of gypsum-based self-leveling mainly use α semi-hydrated high-strength gypsum, building gypsum and anhydrite. Gypsum-based self-leveling mortar can be divided into the following three types: high-strength gypsum-based self-leveling mortar, building gypsum self-leveling mortar, anhydrite self-leveling mortar.

[0005] At present, the gypsum-based self-leveling materials on the market, which are made from industrial by-product gypsum, are mainly building gypsum. The quality of the products varies greatly, and there are problems such as low strength, poor water resistance, short setting time, easy frost and mold in the products. However, the water resistance and rheology of anhydrite are much better than those of building gypsum.

[0006] The technology of so-called anhydrite self-leveling mortar in the prior art has the following problems. (1) It is necessary to prepare the self-leveling by adding semi-hydrated gypsum or other cementitious materials, so that the anhydrite dosage is small and the utilization rate is low. This type of material is essentially a semi-hydrated gypsum-based self-leveling material or a cement-based self-leveling material. (2) Anhydrous anhydrite itself has a slow hydration rate and a long setting time, and requires a high-efficiency stimulator to ensure its own hydration strength and cementitious properties. These problems lead to the defects of unstable material properties, low mechanical properties, and poor construction properties, and their application is greatly limited. Therefore, a high-dosage anhydrite-based self-leveling material has been developed. The material has a large anhydrite dosage, a high utilization rate, stable performance, and excellent construction performance. Summary of the invention

[0007] The purpose of the present invention is to provide an anhydrite-based self-leveling material, which solves the problem that anhydrite is slow to hydrate and harden, and the gelling properties are difficult to exert. At present, there are almost no self-leveling mortar products on the market that use anhydrite II as the main gelling material. The anhydrite utilization rate in the self-leveling material is high, and at the same time, it provides a high-value-added way to process a large amount of anhydrite.

[0008] The present invention is achieved through the following technical solutions:

[0009] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0010] Type II anhydrous gypsum: 80 parts

[0011] 42.5 Gray cement: 12-16 parts

[0012] Rapid hardening cement: 4-8 parts

[0013] Salt compound activator: 2.7-3.7 parts

[0014] Sand: 10-16 parts

[0015] Water reducing agent: 0.3-0.4 parts

[0016] In dispersible latex powder: 0-1 part

[0017] Water-retaining thickener: 0.03-0.1 parts

[0018] Defoamer: 0.08-0.12 parts

[0019] Water: 25-28 parts

[0020] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the anhydrous anhydrite is mainly composed of type II anhydrous anhydrite, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous anhydrite is as follows:

[0021]

[0022] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the 42.5 gray cement is ordinary Portland cement.

[0023] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40% to 50%, Al2O3 25% to 40%, SiO25% to 10%, Fe2O3 2% to 3%, SO3 7% to 9%, and MgO 1% to 3%.

[0024] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0025] A further technical solution of the anhydrous anhydrite-based self-leveling material of the present invention is that the sand is fine yellow sand with a particle size of 0.125 mm to 0.25 mm.

[0026] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0027] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the dispersible latex powder is at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer, and acrylic copolymer.

[0028] The anhydrous anhydrite-based self-leveling material of the present invention has a further technical solution that the water-retaining thickener is any one of cellulose ether and hydroxypropyl methylcellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0029] A further technical solution of the anhydrous anhydrite-based self-leveling material of the present invention is that the defoamer is any one of a polyether siloxane copolymer and an organosilicon defoamer.

[0030] The anhydrite-based self-leveling material of the present invention further comprises the following steps: anhydrite, 425 cement, quick-hardening cement, sand, activator, water reducer, rubber powder, water-retaining thickener, and defoamer are mixed and stirred evenly for 3-5 minutes to obtain a self-leveling dry powder material. Then, the self-leveling dry powder material and water are added to a mixer and stirred for 1-3 minutes to obtain anhydrite-based self-leveling material.

[0031] The beneficial effects of the present invention are as follows: 80% natural type II anhydrous hard gypsum is used as the main raw material to prepare the hard gypsum-based self-leveling material. The hard gypsum production process does not require high-temperature calcination, which is energy-saving and environmentally friendly. It has the characteristics of light weight and sound insulation, and its performance is more stable and controllable than that of industrial by-product gypsum. The hard gypsum content is large and the utilization rate is high.

[0032] The invention incorporates a self-made composite sulfate activator, which is simple to prepare and easy to obtain, and can fully activate anhydrite and improve its activity.

[0033] The natural anhydrous hard gypsum-based self-leveling material adopts a chemical excitation method to compound a homemade sulfate activator and an alkaline activator to synergistically activate the hard gypsum. The prepared material has high mechanical strength, good water resistance and small dimensional change. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0037] Type II anhydrous gypsum: 80 parts

[0038] 42.5 Gray cement: 16 parts

[0039] Rapid hardening cement: 4 parts

[0040] Salt compound activator: 2.7 parts

[0041] Sand: 16 parts

[0042] Water reducing agent: 0.38 parts

[0043] Dispersible latex powder: 1 part

[0044] Water-retaining thickener: 0.1 part

[0045] Defoaming agent: 0.1 part

[0046] Water: 25 parts

[0047] Among them, anhydrous gypsum is mainly composed of type II anhydrous gypsum, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous gypsum is as follows:

[0048]

[0049] 42.5 Gray cement is ordinary Portland cement.

[0050] Rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%~50%, Al2O325%~40%, SiO2 5%~10%, Fe2O3 2%~3%, SO3 7%~9%, and MgO 1%~3%.

[0051] The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0052] The sand is fine yellow sand with a particle size of 0.125mm to 0.25mm.

[0053] The water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0054] The dispersible latex powder may be at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic copolymer.

[0055] The water-retaining thickener is any one of cellulose ether and hydroxypropyl methyl cellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0056] The defoaming agent is any one of a polyether siloxane copolymer and an organosilicon defoaming agent.

[0057] Weigh the mass parts of the above raw materials. Take anhydrous hard gypsum as the main raw material, add 425 silicate cement and sulphoaluminate rapid hardening cement to obtain the main hard gypsum binder, and add fine sand.

[0058] Add salt composite activator, water reducing agent, dispersible latex powder, water-retaining thickener and defoamer into the binder and mix thoroughly. Stir evenly for 3-5 minutes to obtain self-leveling dry powder material.

[0059] Then, the self-leveling dry powder material and water were added to the mixer and stirred for 3-5 minutes to obtain an anhydrous anhydrite-based self-leveling material. The prepared anhydrous anhydrite-based self-leveling material was subjected to performance tests at corresponding ages, and the test results are shown in Table 1 below.

[0060] Example 2

[0061] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0062] Type II anhydrous gypsum: 80 parts

[0063] 42.5 Gray cement: 16 parts

[0064] Rapid hardening cement: 4 parts

[0065] Salt compound activator: 2.7 parts

[0066] Sand: 16 parts

[0067] Water reducing agent: 0.38 parts

[0068] Water-retaining thickener: 0.1 part

[0069] Defoaming agent: 0.2 parts

[0070] Water: 25 parts

[0071] Among them, anhydrous gypsum is mainly composed of type II anhydrous gypsum, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous gypsum is as follows:

[0072]

[0073] 42.5 Gray cement is ordinary Portland cement.

[0074] Rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%~50%, Al2O325%~40%, SiO2 5%~10%, Fe2O3 2%~3%, SO3 7%~9%, and MgO 1%~3%.

[0075] The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0076] The sand is fine yellow sand with a particle size of 0.125mm to 0.25mm.

[0077] The water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0078] The dispersible latex powder may be at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic copolymer.

[0079] The water-retaining thickener is any one of cellulose ether and hydroxypropyl methyl cellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0080] The defoaming agent is any one of a polyether siloxane copolymer and an organosilicon defoaming agent.

[0081] Weigh the mass parts of the above raw materials. Take anhydrous hard gypsum as the main raw material, add 425 silicate cement and sulphoaluminate rapid hardening cement to obtain the main hard gypsum binder, and add fine sand.

[0082] Add salt composite activator, water reducing agent, dispersible latex powder, water-retaining thickener and defoamer into the binder and mix thoroughly. Stir evenly for 3-5 minutes to obtain self-leveling dry powder material.

[0083] Then, the self-leveling dry powder material and water were added to the mixer and stirred for 3-5 minutes to obtain an anhydrous anhydrite-based self-leveling material. The prepared anhydrous anhydrite-based self-leveling material was subjected to performance tests at corresponding ages, and the test results are shown in Table 1 below.

[0084] Example 3

[0085] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0086] Type II anhydrous gypsum: 80 parts

[0087] 42.5 Gray cement: 12 parts

[0088] Rapid hardening cement: 8 parts

[0089] Salt compound stimulant: 3.5 parts

[0090] Sand: 10 parts

[0091] Water reducing agent: 0.38 parts

[0092] Water-retaining thickener: 0.03 parts

[0093] Defoaming agent: 0.1 part

[0094] Water: 28 parts

[0095] Among them, anhydrous gypsum is mainly composed of type II anhydrous gypsum, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous gypsum is as follows:

[0096]

[0097] 42.5 Gray cement is ordinary Portland cement.

[0098] Rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%~50%, Al2O325%~40%, SiO2 5%~10%, Fe2O3 2%~3%, SO3 7%~9%, and MgO 1%~3%.

[0099] The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0100] The sand is fine yellow sand with a particle size of 0.125mm to 0.25mm.

[0101] The water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0102] The dispersible latex powder may be at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic copolymer.

[0103] The water-retaining thickener is any one of cellulose ether and hydroxypropyl methyl cellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0104] The defoaming agent is any one of a polyether siloxane copolymer and an organosilicon defoaming agent.

[0105] Weigh the mass parts of the above raw materials. Take anhydrous hard gypsum as the main raw material, add 425 silicate cement and sulphoaluminate rapid hardening cement to obtain the main hard gypsum binder, and add fine sand.

[0106] Add salt composite activator, water reducing agent, dispersible latex powder, water-retaining thickener and defoamer into the binder and mix thoroughly. Stir evenly for 3-5 minutes to obtain self-leveling dry powder material.

[0107] Then, the self-leveling dry powder material and water were added to the mixer and stirred for 3-5 minutes to obtain an anhydrous anhydrite-based self-leveling material. The prepared anhydrous anhydrite-based self-leveling material was subjected to performance tests at corresponding ages, and the test results are shown in Table 1 below.

[0108] Example 4

[0109] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0110] Type II anhydrous gypsum: 80 parts

[0111] 42.5 Gray cement: 16 parts

[0112] Rapid hardening cement: 4 parts

[0113] Salt compound activator: 2.7 parts

[0114] Sand: 16 parts

[0115] Water reducing agent: 0.38 parts

[0116] Dispersible latex powder: 2 parts

[0117] Water-retaining thickener: 0.05 parts

[0118] Defoaming agent: 0.1 part

[0119] Water: 25 parts

[0120] Among them, anhydrous gypsum is mainly composed of type II anhydrous gypsum, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous gypsum is as follows:

[0121]

[0122] 42.5 Gray cement is ordinary Portland cement.

[0123] Rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%~50%, Al2O325%~40%, SiO2 5%~10%, Fe2O3 2%~3%, SO3 7%~9%, and MgO 1%~3%.

[0124] The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0125] The sand is fine yellow sand with a particle size of 0.125mm to 0.25mm.

[0126] The water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0127] The dispersible latex powder may be at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic copolymer.

[0128] The water-retaining thickener is any one of cellulose ether and hydroxypropyl methylcellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0129] The defoaming agent is any one of a polyether siloxane copolymer and an organosilicon defoaming agent.

[0130] Weigh the mass parts of the above raw materials. Take anhydrous hard gypsum as the main raw material, add 425 silicate cement and sulphoaluminate rapid hardening cement to obtain the main hard gypsum binder, and add fine sand.

[0131] Add salt composite activator, water reducing agent, dispersible latex powder, water-retaining thickener and defoamer into the binder and mix thoroughly. Stir evenly for 3-5 minutes to obtain self-leveling dry powder material.

[0132] Then, the self-leveling dry powder material and water were added to the mixer and stirred for 3-5 minutes to obtain an anhydrous anhydrite-based self-leveling material. The prepared anhydrous anhydrite-based self-leveling material was subjected to performance tests at corresponding ages, and the test results are shown in Table 1 below.

[0133] Example 5

[0134] An anhydrous hard gypsum-based self-leveling material is composed of the following raw materials in parts by weight:

[0135] Type II anhydrous gypsum: 80 parts

[0136] 42.5 Gray cement: 12 parts

[0137] Rapid hardening cement: 8 parts

[0138] Salt composite activator: 3.7 parts

[0139] Sand: 16 parts

[0140] Water reducing agent: 0.38 parts

[0141] Water-retaining thickener: 0.03 parts

[0142] Defoaming agent: 0.1 part

[0143] Water: 28 parts

[0144] Among them, anhydrous gypsum is mainly composed of type II anhydrous gypsum, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical composition mass composition of the anhydrous gypsum is as follows:

[0145]

[0146] 42.5 Gray cement is ordinary Portland cement.

[0147] Rapid-hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%~50%, Al2O325%~40%, SiO2 5%~10%, Fe2O3 2%~3%, SO3 7%~9%, and MgO 1%~3%.

[0148] The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 2-2.5:1.

[0149] The sand is fine yellow sand with a particle size of 0.125mm to 0.25mm.

[0150] The water reducer is at least one of a polycarboxylic acid-based high-performance water reducer, a naphthalene-based high-efficiency water reducer and an amino-based high-efficiency water reducer;

[0151] The dispersible latex powder may be at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate vinyl copolymer, and acrylic copolymer.

[0152] The water-retaining thickener is any one of cellulose ether and hydroxypropyl methyl cellulose ether, and the viscosity of the water-retaining agent is less than 4000 mpa·s.

[0153] The defoaming agent is any one of a polyether siloxane copolymer and an organosilicon defoaming agent.

[0154] Weigh the mass parts of the above raw materials. Take anhydrous hard gypsum as the main raw material, add 425 silicate cement and sulphoaluminate rapid hardening cement to obtain the main hard gypsum binder, and add fine sand.

[0155] Add salt composite activator, water reducing agent, dispersible latex powder, water-retaining thickener and defoamer into the binder and mix thoroughly. Stir evenly for 3-5 minutes to obtain self-leveling dry powder material.

[0156] Then, the self-leveling dry powder material and water were added to the mixer and stirred for 3-5 minutes to obtain an anhydrous anhydrite-based self-leveling material. The prepared anhydrous anhydrite-based self-leveling material was subjected to performance tests at corresponding ages, and the test results are shown in Table 1 below.

[0157] Table 1 Performance test results of various embodiments

[0158] project Example 1 Example 2 Example 3 Example 4 Example 5 30min fluidity / mm 163 160 165 157 148 24h flexural strength / MPa 2.2 2.1 2.0 2.2 2.3 24h compressive strength / MPa 10.5 9.8 10.0 9.8 10.3 28d absolute dry flexural strength / MPa 10.3 9.6 9.5 9.9 10.2 28d absolute dry compressive strength / MPa 41.5 38.9 41.3 42.4 42.3 28d drying tensile bond strength / MPa 1.43 1.22 1.57 1.68 1.63 Dimensional change rate / % 0.03 0.03 0.02 0.02 0.01 Impact resistance qualified qualified qualified qualified qualified

[0159] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-dosage anhydrous hard gypsum-based self-leveling material, characterized in that: It is composed of the following raw materials by weight: Type II anhydrous gypsum: 80 parts; 42.5 Gray cement: 12-16 parts; Rapid hardening cement: 4-8 parts; Salt composite stimulant: 2.7-3.7 parts; Sand: 10-16 parts; Water reducing agent: 0.3-0.4 parts; In dispersible latex powder: 0-1 part; Water-retaining thickener: 0.03-0.1 parts; Defoaming agent: 0.08-0.12 parts; Water: 25-28 parts.

2. A high-dosage anhydrite-based self-leveling material according to claim 1, characterized in that: The anhydrous anhydrite is mainly composed of type II anhydrous anhydrite, containing a small amount of dihydrate gypsum, dolomite and clay minerals. The main chemical components of the anhydrous anhydrite are 37.15% CaO, 48.69% SO3, 1.50% Fe2O3, 2.98% Al2O3, 5.88% SiO2 and 3.18% MgO.

3. A high-dosage anhydrite-based self-leveling material according to claim 2, characterized in that: The 42.5 gray cement is ordinary Portland cement.

4. A high-dosage anhydrite-based self-leveling material according to claim 3, characterized in that: The rapid hardening cement is sulphoaluminate cement, and its chemical mass composition is CaO 40%-50%, Al2O3 25%-40%, SiO2 5%-10%, Fe2O3 2%-3%, SO3 7%-9%, and MgO 1%-3%.

5. A high-dosage anhydrite-based self-leveling material according to claim 4, characterized in that: The salt composite activator is composed of anhydrous potassium sulfate and anhydrous sodium sulfate, and the mass ratio thereof is 1.8-3:

1.

6. A high-dosage anhydrite-based self-leveling material according to claim 5, characterized in that: The sand is fine yellow sand with a particle size of 0.125 mm to 0.25 mm.

7. A high-dosage anhydrite-based self-leveling material according to claim 6, characterized in that: The water reducer is at least one of a polycarboxylic acid high-performance water reducer, a naphthalene high-efficiency water reducer and an amino high-efficiency water reducer.

8. A high-dosage anhydrite-based self-leveling material according to claim 7, characterized in that: The dispersible latex powder is at least one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer and acrylic copolymer.

9. A high-dosage anhydrite-based self-leveling material according to claim 8, characterized in that: The water-retaining thickener is any one of cellulose ether and hydroxypropyl methylcellulose ether, the viscosity of the water-retaining agent is less than 4000 mpa·s, and the defoaming agent is any one of polyether siloxane copolymer and organosilicon defoaming agent.

Citation Information

Patent Citations

  • Natural anhydrite self-leveling anti-crack mortar

    CN115368101A